Incidence, risk factors and outcomes of atrial arrhythmias in adult patients with atrioventricular septal defect. (24th May 2021) - Jacquemart, E; Bessiere, F; Combes, N; Ladouceur, M; Iserin, L; Gardey, K; Henaine, R; Chevalier, P; Legendre, A; Petit, J; Di Filippo, S; Hascoet, S; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Public Institution(s). Main funding source(s): French Federation of Cardiology Background: The number of adults with atrioventricular septal defects (AVSD) is growing, with however, very few data regarding the natural history of atrial arrhythmias in this specific population. We aimed to assess the incidence, associated factors and outcomes of atrial arrhythmias among adult patients with AVSD. Methods: Multicentric retrospective cohort of patients with AVSD from 3 referral centers specialized in adult congenital heart disease. Unbalanced AVSD, univentricular hearts, and Eisenmenger syndromes were excluded. Lifetime cumulative incidences of different types of atrial arrhythmia (>30 seconds) were analyzed (atrial fibrillation [AF] and intra atrial reentrant tachycardia/focal atrial tachycardia [IART/FAT]). Multiple logistic regression models were used to identify risk factors for atrial arrhythmias. Results: The cohort comprised of 391 patients (61.6% of women) with a mean age of 36.3 ± 16.3 years and 17.3 ± 14.2 years of follow-up after surgical repair in operated patients, including 333 (85.1%) partial/intermediate and 58 (1.0%) complete AVSD. Overall, atrial arrhythmias were documented in 98 patients (25.1%). The lifetime risks for developing atrial arrhythmia to ages 20, 40, and 60 were 3.7%, 17.6%, and 54.8%. IART/FAT was the leading arrhythmia until the age of 45 then AF surpassed IART/FAT. Age (OR = 1.4, 95%CI = 1.2-1.6 by 5 years increment), the number of cardiac surgeries (OR = 4.1, 95%CI = 2.5-6.9), left atrial dilatation (OR = 3.1, 95%CI = 1.4-6.8), right atrial dilatation (OR = 4.1, 95%CI = 1.7-10.3), and moderate or severe left AV valve regurgitation (OR = 3.7, 95%CI = 1.2-11.7) were independently associated with a higher risk of atrial arrhythmias. Patients with atrial arrhythmias more frequently had pacemaker implantation (41.8% vs. 8.5%, p < 0.001), heart failure (24.5% vs 1.0%, p < 0.001) and cerebrovascular accidents (11.2% vs 3.4%, p = 0.007). Conclusions: The lifetime risk of atrial arrhythmias in patients with AVSD is considerable with more than half of patients who will develop an atrial arrhythmia by the age of 60. Atrial arrhythmias are associated with a significant morbidity in this population.